Gaya Komunikasi Pimpinan Gen Z di Hawa Modelling School: Studi Kasus dalam Meningkatkan Kinerja Karyawan Tahun 2024 - Muhammad Satria Permana; Mochammad Mirza; Ajeng Pradesti (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
In a company, the communication style of a leader plays a crucial role, especially in addressing organizational problems such as a decline in employee performance. Using an inappropriate communication style may complicate the internal dynamics of the company and hinder efforts to resolve performance-related issues. The purpose of this study is to explore the communication style of a Generation Z leader in improving employee performance at Hawa Modelling School. This research employs a qualitative approach by collecting data through interviews, observations, and documentation. The findings indicate that the Gen Z leader at Hawa Modelling School adopts a two-way and open communication style to foster participative discussions and encourage employees to express suggestions and solutions regarding performance decline. A dynamic communication style is used to give appreciation and boost employee morale, while a structured style is applied when delivering instructions systematically to ensure focused and productive discussions. These four communication styles contribute to creating a comfortable work environment that supports improved employee performance.